Venice Design 2017. - Dorigo, Nina; Guibaud, Camille; Hammoud, Anaïs; European Cultural Centre ([S.l.] : GAA Foundation, 2017)
Beger, Eckhard ; Bentes Simas, Gisela ; Browning, Jonathan ; Buchfelder, Heike ; Casinni, Luca ; Ciffo, Alessandro ; Denys, Anton Hendrik ; Bähring, Ulrich ; Bertheau, Björn ; Elizarova, Ekaterina ; Erceg, Vedran ; Hellgren, Marie-Louise ; Hervet, Cédric & Nicolas ; Higham, Steen ; Hofman, Florentijn [et al.]
Venice Design 2017, Palazzo Michiel - Palazzo Rossini, Venice, 13 May - 26 November 2017
boek